2022
DOI: 10.3390/antiox11071295
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Insulin Resistance in Hyperthyroid Rat Liver: Vitamin E Supplementation Highlights a Possible Role of ROS

Abstract: Thyroid hormones are normally involved in glycaemic control, but their excess can lead to altered glucose metabolism and insulin resistance (IR). Since hyperthyroidism-linked increase in ROS results in tissue oxidative stress that is considered a hallmark of conditions leading to IR, it is conceivable a role of ROS in the onset of IR in hyperthyroidism. To verify this hypothesis, we evaluated the effects of vitamin E on thyroid hormone-induced oxidative damage, insulin resistance, and on gene expression of key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 74 publications
(78 reference statements)
1
15
1
Order By: Relevance
“…However, the results from the group fed a diet with buriti oil (BFe) suggest that the oil chemical composition was efficient to minimize the deleterious effect of the high-FeSO 4 dose on antioxidant enzyme activity. This result agrees with studies in which GPx and SOD activity evaluation in animals and humans with a β-carotene- or α-tocopherol-supplemented diet indicated the expression and activity of these enzymes, probably because of the compensatory defense of oxidative stress [ 64 , 65 , 66 , 67 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the results from the group fed a diet with buriti oil (BFe) suggest that the oil chemical composition was efficient to minimize the deleterious effect of the high-FeSO 4 dose on antioxidant enzyme activity. This result agrees with studies in which GPx and SOD activity evaluation in animals and humans with a β-carotene- or α-tocopherol-supplemented diet indicated the expression and activity of these enzymes, probably because of the compensatory defense of oxidative stress [ 64 , 65 , 66 , 67 ].…”
Section: Discussionsupporting
confidence: 91%
“…The high contents of β-carotene and α-tocopherol quantified in buriti oil contribute to the significant in vitro antioxidant capacity, which in turn can attenuate oxidative damage with consequent tissue recovery and biomolecules. β-carotene can quench singlet oxygen, α-tocopherol reduces mitochondrial hydrogen peroxide release rate, and both react as ROS scavengers in a nonenzymatic manner to prevent or decrease oxidative damage to biomolecules and cells [ 50 , 65 , 66 , 67 , 68 ]. Furthermore, a previous study demonstrated the synergism action among oleic acid and α-tocopherol to prevent oxidative stress [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides β-cell damage and/or dysfunction, oxidative stress is also one of the important triggers of insulin resistance [ 44 , 45 , 46 ]. During insulin signaling transduction, insulin stimulates autophosphorylation of the insulin receptor thereby phosphorylating and activating insulin receptor substrate, which subsequently activates phosphatidylinositol 3-kinase (PI3K) as well as the downstream phosphoinositide-dependent protein kinase-1 (PDK1) and AKT [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid and protein oxidative damages were determined in both muscle homogenates and mitochondria by determining the lipid hydroperoxides (Hps) levels [ 20 ], and protein-bound carbonyls (CO) [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…After exposure of homogenates and mitochondria to Fe and ascorbate (Fe/Asc, 100/1000 μM, respectively) for 10 min, the susceptibility to oxidative stress was assessed by measuring the changes in hydroperoxides content [ 22 ].…”
Section: Methodsmentioning
confidence: 99%